Rosemary Extract Reduces Odor in Cats Through Nitrogen and Sulfur Metabolism by Gut Microbiota–Host Co-Modulation - Ziming Huang; Miao Li; Zhiqin He; Xiliang Yan; Yinbao Wu; Peiqiang Mu; Jun Jiang; Xu Wang; Yan Wang (Animals, 2025)
Odors from pet cats can negatively affect the quality of life of cat owners. The diverse bioactive compounds in plant extracts make them a promising candidate for effective odor reduction. This study evaluated twelve plant extracts for deodorizing efficacy via in vitro fermentation tests. Rosemary extract and licorice extract exhibited better deodorizing effects, with fractions of rosemary extract below 100 Da demonstrating the most effective deodorizing performance. Based on these findings, subsequent feeding trials were conducted using rosemary extract and its fractions below 100 Da. In the feeding trial, adult British Shorthair cats were divided into three groups (Control Check, RE, and RE100) and housed in a controlled-environment respiration chamber for 30 days. Measurements included odor emissions, fecal and blood physicochemical parameters, immune parameters, microbiota composition based on 16S rRNA sequencing, and metabolome analysis. The results of the feeding trial indicated that rosemary extract significantly reduced ammonia and hydrogen sulfide emissions (46.84%, 41.64%), while fractions below 100 Da of rosemary extract achieved even greater reductions (55.62%, 53.87%). Rosemary extract regulated the intestinal microbial community, significantly increasing the relative abundance of the intestinal probiotic Bifidobacterium (p < 0.05) and reducing the population of sulfate-reducing bacteria (p < 0.05). It also significantly reduced urease and uricase activities (p < 0.05) to reduce ammonia production and inhibited the degradation of sulfur-containing proteins and sulfate reduction to reduce hydrogen sulfide emissions. Furthermore, rosemary extract significantly enhanced the immune function of British Shorthair cats (p < 0.05). This study suggests that rosemary extract, particularly its fractions below 100 Da, is a highly promising pet deodorizer.